COVD-13. EFFECTS OF COVID-19 PANDEMIC ON NEUROSURGICAL ONCOLOGY PRACTICES AT INOVA HEALTH SYSTEM: AN INSTITUTIONAL EXPERIENCE. (9th November 2020) - Dang, Danielle; Mugge, Luke; Awan, Omar; Gunnells, Emily; Vaughan, Megan; Ziu, Mateo
Abstract: INTRODUCTION: Amidst the unprecedented nationwide ban on elective surgeries during the COVID-19 pandemic, concern regarding timely and safe treatment of patients with intracranial tumors has been raised in the neuro-oncology community. METHODS: A retrospective chart review was performed on all patients who underwent treatment for intracranial tumors from 3/12–7/1 for 2019 and 2020. Dates aligned with declaration of State of Emergency through the multi-phase public re-opening. Primary comparative endpoints included case volume, median time to surgery, chemotherapy, and radiation, and COVID-related mortality. RESULTS: Overall surgical case volume decreased by 26.6%, while a 46.9% decrease was evident during the ban on elective surgeries. Case reduction occurred only for glial (p= 0.33) and pituitary tumors (p=0.04) where volume was nearly identical for other tumors. Median time to surgery was 2.5 days (range: 0–9) for high-grade glioma patients, 3 days for metastases, 3 days for meningiomas, and 26 days (range: 0–98) for pituitary adenomas, not significantly different from 2019. Time to chemoradiation and planned number of treatments were without significant difference. Among 2, 795 Covid-19 patients treated in our institution, only four had brain tumors. Only one patient experienced delayed radiation treatment (three weeks) due to inability to achieve seroconversion prior to planned simulation. Only one COVID-related mortality in our cohort occurred. DISCUSSION: The pandemic did not significantly delay type and time to treatment for neuro-oncology patients at Inova. With swift implementation of PPE and strict peri-operative testing, we provided standard of care treatment without increases in COVID-19 contraction or mortality. Decreases in overall case volume are likely due to ongoing cultural avoidance of seeking medical care; deferment of endonasal surgery may be attributed to a known greater mortality for ENT procedures. Future patient care challenges include establishing clinical significance of seroconversion for asymptomatic, COVID-19 infected patients without delaying necessary systemic treatment.